Arab Culture and Community at Al-maun Muhammadiyah Boarding School - Muvida , Fika; Hikmah , Khizanatul (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The promotion of Arabic language proficiency is crucial in Islamic educational institutions, particularly in boarding schools. Specific Background: At the S-PEAM Putri Islamic Boarding School in Pasuruan City, the concept of Arabiyah bi'ah encompasses both formal and non-formal methods of language acquisition, yet the effectiveness of these implementations remains underexplored. Knowledge Gap: Existing literature lacks comprehensive qualitative analyses that address both the supporting and inhibiting factors affecting language acquisition in such settings. Aims: This study aims to investigate the implementation of Arabiyah bi'ah at S-PEAM Putri and identify the factors that contribute to or hinder its effectiveness. Results: The research reveals two distinct types of Arabiyah bi'ah: formal practices, which involve structured lessons focusing on grammar and vocabulary, and non-formal practices, such as language circles and multimedia engagement. Internal supporting factors include self-awareness and discipline, while external factors encompass environmental influences and instructional support. Inhibiting factors identified include a lack of motivation and external distractions such as family visits and curriculum inconsistencies. Novelty: This study employs a qualitative descriptive approach, utilizing Milles and Huberman's analytical techniques and SWOT analysis to provide a nuanced understanding of the dynamics within the boarding school context. Implications: Findings underscore the importance of fostering a supportive environment for Arabic language acquisition, highlighting the need for consistent implementation of language practices to enhance student engagement and proficiency. Highlights: Types of Arabiyah Bi'ah: The study identifies formal and non-formal practices that facilitate Arabic language learning among students. Supporting Factors: Internal factors like self-awareness and discipline, along with external influences, significantly enhance language acquisition. Inhibiting Challenges: Factors such as lack of motivation and external distractions hinder effective language development. Keywords: Arabiyah bi'ah, Islamic boarding school, language acquisition, supporting factors, inhibiting factors.